THE STUDY ON MANGROVE LITTERS AS A SOURCE OF NUTRIENTS FOR BLANAKAN MANGROVE POND, SUBANG, WEST JAVA - Joni Haryadi; Adi Basukriadi; Muhadiono Muhadiono (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
Mangrove litters as a source of nutrients for sylvofishery pond (TS), sedimented pond (TT), and conservation pond (TP) was studied at Blanakan mangrove pond during April until June 2008. The variables of study were litter production, litter decomposition, and dissolved nutrients (ammonium, nitrite, nitrate, and phosphate). The obtained data were analyzed using F test and continued using Least Significant Different (LSD). The results showed that litter production at TS, TT, and TP were 19.55±4.34 ton/ha/year, 15.90±1.98 ton/ha/year, and 21.67±1.89 ton/ha/year respectively. The decomposition rate at TS, TT, and TP was 0.051±0.038, 0.051±0.018, and 0.081±0.041, respectively. Mangrove litters were potentially as a source of dissolved nutrients at Blanakan mangrove pond. Increasing both litter production and decomposition rate could increase ammonium, nitrite, and phosphate. Therefore, mangrove litters were play role for determined the fertility at Blanakan mangrove pond.